Long-term CIDR program for synchronization of estrus in beef heifers produces acceptable AI pregnancy rates - Johnson, Sandra K.; Bolte, J.W.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Routinely achieving pregnancy rates greater than 50% with fixed-time artificial insemination (AI) in heifers has been difficult. The Beef Reproduction Task Force recently added the intravaginal progesterone-releasing device (CIDR)-Select to its list of recommended fixed-time AI protocols. Research and field trials in Missouri have achieved AI pregnancy rates in the range of 55% to 60%. Another relatively new protocol is the 5-day CO-Synch, a timed AI protocol + CIDR that has produced pregnancy rates similar to or higher than those obtained with the standard 7-day CO-Synch + CIDR protocol. It is not known whether these two systems differ in terms of estrous response. The objective of the current study was to compare effects of a long-term, 14-day CIDR-Select protocol and a 5-day CO-Synch + CIDR protocol on estrous distribution and AI pregnancy rate in yearling beef heifers.
Keywords: Beef; CIDR; Estrus; Heifers; AI; Pregnancy rates